2022
DOI: 10.1002/jmv.27596
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of high‐frequency RBD mutations of SARS‐CoV‐2 with three VOCs did not cause significant antigenic drift

Abstract: Variants of SARS-CoV-2 continue to emerge, posing great challenges in outbreak prevention and control. It is important to understand in advance the impact of possible variants of concern (VOCs) on infectivity and antigenicity.Here, we constructed one or more of the 15 high-frequency naturally occurring amino acid changes in the receptor-binding domain (RBD) of Alpha, Beta, and Gamma variants. A single mutant of A520S, V367F, and S494P in the above three VOCs enhanced infectivity in ACE2-overexpressing 293T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 54 publications
(116 reference statements)
1
6
0
Order By: Relevance
“…Additionally, Lassaunière et al found that lineages with E484K showed a significant reduction in virus neutralization titers relative to D614G (4.0-fold) and other Delta strains tested, including B.1.617.2 (2.3-fold), AY.4 (2.3-fold), and AY.4.2 (1.7-fold) [ 46 ]. Li, et.al observed that additional S494P showed increased Alpha and Beta variants infectivity [ 47 ]. Our analysis indicates that there is a possibility of antibody escape synergy for the S:E484K and S:S494P combination.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Lassaunière et al found that lineages with E484K showed a significant reduction in virus neutralization titers relative to D614G (4.0-fold) and other Delta strains tested, including B.1.617.2 (2.3-fold), AY.4 (2.3-fold), and AY.4.2 (1.7-fold) [ 46 ]. Li, et.al observed that additional S494P showed increased Alpha and Beta variants infectivity [ 47 ]. Our analysis indicates that there is a possibility of antibody escape synergy for the S:E484K and S:S494P combination.…”
Section: Discussionmentioning
confidence: 99%
“…NiV pseudovirus neutralization was measured by a reduction in luciferase expression, as previously described in the new coronavirus pseudovirus neutralization assay ( Li et al, 2022 ). The serum dilution corresponding to a 50% inhibitory dilution was defined as the amount of half inhibition (ID50).…”
Section: Methodsmentioning
confidence: 99%
“…A decrease in temperature correlates with increased persistence of viable SARS‐CoV‐2 on abiotic surfaces while very low (20% or less) and very high (80% or more) relative humidity increases virus inactivation and average (20–80%) relative humidity prolongs virus persistence (Biryukov et al, 2020; Kwon et al, 2021a). Some studies have shown there is no significant difference in SARS‐CoV‐2 persistence on different abiotic surfaces, but others found there was a more rapid reduction in viability on fabric or metal surfaces compared to plastics or glass (Biryukov et al, 2020; Gidari et al, 2021; Li et al, 2023; Pastorino et al, 2020; Van Doremalen et al, 2020). The composition of the inoculum also contributes to SARS‐CoV‐2 persistence on surfaces with addition of protein to the virus media increasing its persistence, whereas the addition of some bodily fluids decrease its persistence (Kwon et al, 2021b; Matson et al, 2020; Pastorino et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The persistence of viable SARS‐CoV‐2 on biotic surfaces has been less extensively investigated than abiotic surfaces but decreased temperature causes prolonged viability (Dai et al, 2021; Dhakal et al, 2021; Feng et al, 2021; Jung et al, 2023; Li et al, 2023). SARS‐CoV‐2 viability on biotic surfaces has been shown to vary between different foods, with a reduction in viability when incubated on foods such as avocado, mushroom, and salmon compared to other foods such as poultry, pork, and cheese (Dhakal et al, 2021; Feng et al, 2021; M. Jia et al, 2022; Li et al, 2023). SARS‐CoV‐2 has been shown to remain viable when contaminated foods are exposed to heat, though high temperatures do inactivate virus (M. Jia et al, 2022; Norouzbeigi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%